Search Strategies for Finding Reports of Research - Charbonneau, Deborah; Walster, Dian; Kumasi, Kafi (Qualitative and Quantitative Methods in Libraries, 2019)
The purpose of this study was to test various search strategies for locating reports of research in the extant literature. Implications from the findings of this study are generalized into recommendations for how academic librarians can apply their professional skill sets to aid students whether undergraduate, graduate, profession or doctoral to effectively find reports of research. More specifically, the concept of “research hooks” is presented as a way for librarians to help students craft more effective database search strategies. Research hooks are complementary words to leverage database searching and identify reports of research in the literature. This recommended search strategy presents an opportunity for librarians to play an important role and assist students with constructing effective search strategies